2019
DOI: 10.1177/2377960819844670
|View full text |Cite
|
Sign up to set email alerts
|

Informal Caregiving in a Medically Underserved Community: Challenges, Construction of Meaning, and the Caregiver–Recipient Dyad

Abstract: Little is known about informal caregivers' challenges in medically underserved communities. This qualitative study explores their perceptions/experiences of caregiving in a medically underserved community in Midwest United States. Two focus groups (n ¼ 12) were conducted and themes were extracted and analyzed. Theme 1 included perceived barriers/unmet needs; most prevalent of which were lack of informational resources and support groups. A second unsolicited and unanticipated theme highlighted how caregivers c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…The findings of this study support earlier reports of interindividual variability in meaning making and meanings made (Gibbons et al, 2019; Gorawara-Bhat et al, 2019; Kernan & Lepore, 2009; Lee, 2008; Moye et al, 2020; van der Spek et al, 2013). The between-person variance in meaning factors was higher than the within-person variance in our study, suggesting a substantial between-person difference in meaning, especially meanings made.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings of this study support earlier reports of interindividual variability in meaning making and meanings made (Gibbons et al, 2019; Gorawara-Bhat et al, 2019; Kernan & Lepore, 2009; Lee, 2008; Moye et al, 2020; van der Spek et al, 2013). The between-person variance in meaning factors was higher than the within-person variance in our study, suggesting a substantial between-person difference in meaning, especially meanings made.…”
Section: Discussionsupporting
confidence: 91%
“…The available research—mostly qualitative—has demonstrated variability in meaning making and meanings made in cancer survivors and their caregivers (Gibbons et al, 2019; Gorawara-Bhat et al, 2019; Lee, 2008; van der Spek et al, 2013). A study of oral-digestive cancer survivors, 1-year postdiagnosis, found that approximately half of the study participants engaged in the process of meaning making, or claimed that the disease changed their view on life or its meaning (Moye et al, 2020).…”
Section: Meaning-reconstruction Process In Cancermentioning
confidence: 99%
“…This is important because caregivers are intimately involved in healthcare decision-making, and understanding this influence is vital to enhancing decision-making support and selfmanagement. 14,51,52 This reflection of decision-making supports a relationally-centred and not patient-centred approach, especially when dealing with advanced CKD decisions. 56 Limitations include single-site recruitment, limiting the representation of views where nephrology services may differ.…”
Section: Discussionmentioning
confidence: 75%
“…[12][13][14][15][16] Examples of involvement include engagement with decisions about renal replacement treatment choice, disease management, when to seek emergency care, how to pay for care, obtaining additional help and end-of-life care. 14,15,17,18 As decision support partners, caregivers help patients make decisions by seeking information, communicating, assisting patients to weigh risks and benefits and understand their options, eliciting patients' values, planning for future decisions and implementing decisions. 9,[19][20][21][22][23] To signify the impact of a caregiver's influence, we highlight that studies have demonstrated that family and friends' approval or disapproval influence engagement with preventative cancer screenings and organ donor registration for patients, which signifies the potential weight these individuals have on health-related decision-making.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation